East Africa Public Health Laboratory Networking Project : Evaluation of Performance-Based Financing for Public Health Laboratories in Rwanda - Kumar, Meghan (World Bank, Washington, DC, 2016)
This report summarizes the main findings from the application of performance based incentives linked to progress on a standardized, globally recognized metric - the stepwise laboratory improvement process towards accreditation (SLIPTA) checklist - under the East Africa Public Health Laboratory Networking Project (EAPHLNP) in Rwanda. The lab performance-based financing (PBF) pilot was introduced in the context of a well-established national PBF program dating back to the early 2000s. The flexible nature of the EAPHLNP and the favorable context in Rwanda provided an ideal backdrop to introduce PBF incentive payments to accelerate progress of five project supported labs towards accreditation. The evaluation found improved laboratory performance at all project-supported laboratories in Rwanda as measured by the SLIPTA scores. For the first time, laboratories were bringing in PBF revenues, instilling a culture of continuous quality improvements, and focusing management attention on accreditation. PBF appears to have contributed to an accelerated change, with PBF laboratories experiencing an overall greater increase in SLIPTA scores compared to project-supported laboratories in the other countries. No clear patterns were found in terms of improved test volumes or test accuracy, which were not part of the pilot scheme. While it was difficult to disentangle the effects of different interventions, the evaluation found a system-strengthening value to combining investments in modernizing laboratories, and strengthening human resources with PBF. Relationships between laboratory staff and clinicians improved, with laboratory managers having a greater voice in hospital management and lab staff increasingly valued and respected by clinicians. A spirit of teamwork prevailed at participating sites. Other countries considering PBF mechanisms for public health laboratories need to take into account lessons learned and assess the features which may be relevant to their own contexts. PBF schemes for laboratories need to be viewed as an integral part of a package of interventions that contribute to enhanced performance.